You are what you eat (Sydney : BBC Enterprises Ltd., 1986)
A series of programmes which offer practical advice on how health can be improved dramatically bysimple changes in eating habits. In the light of scientific evidence which links bad diet directly with illness and even death, the series encourages viewers to take positive steps to eat their way to a healthier future
Ep.1- Food for life Ep.2- Go with the grain Ep.3- Dont eat your heart out Ep.4- Sweet nothing
Backup available in VHS 1/2 in.
Copy available in DVD format
Keywords: Diet; Food habits